A Multifaceted Approach to Reduction of Catheter-Associated Urinary Tract Infections in the Intensive Care Unit With an Emphasis on "Stewardship of Culturing". (17th November 2016) - Mullin, Katherine M.; Kovacs, Christopher S.; Fatica, Cynthia; Einloth, Colette; Neuner, Elizabeth A.; Guzman, Jorge A.; Kaiser, Eric; Menon, Venu; Castillo, Leticia; Popovich, Marc J.; Manno, Edward M.; Gordon, Steven M.; et al.
Abstract : BACKGROUND: Catheter-associated urinary tract infections (CAUTIs) are among the most common hospital-acquired infections (HAIs). Reducing CAUTI rates has become a major focus of attention due to increasing public health concerns and reimbursement implications. OBJECTIVE: To implement and describe a multifaceted intervention to decrease CAUTIs in our ICUs with an emphasis on indications for obtaining a urine culture. METHODS: A project team composed of all critical care disciplines was assembled to address an institutional goal of decreasing CAUTIs. Interventions implemented between year 1 and year 2 included protocols recommended by the Centers for Disease Control and Prevention for placement, maintenance, and removal of catheters. Leaders from all critical care disciplines agreed to align routine culturing practice with American College of Critical Care Medicine (ACCCM) and Infectious Disease Society of America (IDSA) guidelines for evaluating a fever in a critically ill patient. Surveillance data for CAUTI and hospital-acquired bloodstream infection (HABSI) were recorded prospectively according to National Healthcare Safety Network (NHSN) protocols. Device utilization ratios (DURs), rates of CAUTI, HABSI, and urine cultures were calculated and compared. RESULTS: The CAUTI rate decreased from 3.0 per 1, 000 catheter days in 2013 to 1.9 in 2014. The DUR was 0.7 in 2013 and 0.68 in 2014. The HABSI rates per 1, 000 patient days decreased from 2.8 in 2013 to 2.4 in 2014. CONCLUSIONS: Effectively reducing ICU CAUTI rates requires a multifaceted and collaborative approach; stewardship of culturing was a key and safe component of our successful reduction efforts. Infect Control Hosp Epidemiol 2017;38:186–188